Stretchable and High‐Performance Fibrous Sensors Based on Ionic Capacitive Sensing for Wearable Healthcare Monitoring - Jiawei Liu; Yan Yang; Guangchuan Chen; Hongbiao Sun; Xin Xie; Yanfeng Hou; Lishen Zhang; Jinhui Wang; Jiangxin Wang (Advanced Science)
Abstract Electronic textiles with remarkable breathability, lightweight, and comfort hold great potential in wearable technologies and smart human‐machine interfaces. Ionic capacitive sensors, leveraging the advantages of the electric double layer, offer higher sensitivity compared to traditional capacitive sensors. Current research on wearable ion‐capacitive sensors has focused mainly on two‐dimensional (2D) or three‐dimensional (3D) device architectures, which show substantial challenges for direct integration with textiles and compromise their wearing experience on conformability and permeability. One‐dimensional (1D) stretchable fiber materials serve as vital components in constructing electronic textiles, allowing for rich structural design, patterning, and device integration through mature textile techniques. Here, a stretchable functional fiber with robust mechanical and electrical performances is fabricated based on semi‐solid metal and ionic polymer, which provided a high stretchability and good electrical conductivity, enabling seamless integration with textiles. Consequently, high‐performance stretchable fiber sensors are developed through different device architecture designs, including pressure sensors with high sensitivity (7.21 kPa−1), fast response (60 ms/30 ms), and excellent stability, as well as strain sensors with high sensitivity (GF = 1.05), wide detection range (0–300% strain), and excellent sensing stability under dynamic deformations.